Upaya Meningkatkan Kemampuan Motorik Halus dengan Menggunakan Media Puzzle pada Anak Tunagrahita di SLB Negeri Manekat Niki-Niki - Djawa, Ade Irma R. Ana; Selan, Ot Bil Wilson; Wangge, Vinsensius; Liunokas, Oded (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Children with mild intellectual disabilities are a group of children with special needs who have an intelligence level ranging from 50 to 70, and often experience difficulties in fine motor skills. One effort that can be made to train fine motor skills as well as eye-hand coordination is through the use of appropriate learning media, one of which is puzzle media. This study aims to improve the fine motor skills of children with mild intellectual disabilities through the use of puzzle media at SLB Negeri Manekat Niki-Niki, Amanuban Tengah District, South Central Timor Regency. The research uses a classroom action method with a quantitative descriptive approach based on Kurt Lewin's model, which consists of planning, action, observation, and reflection stages. The research subjects consisted of three children, comprising two boys and one girl. The data collection technique was conducted through direct observation of students' activities during learning. The data were analyzed quantitatively by calculating the percentage of achievement of fine motor indicators in each cycle. The results showed an improvement in fine motor skills in each cycle after the implementation of puzzle media. Thus, puzzle media has been proven effective in enhancing fine motor skills in mildly mentally retarded children.